A new interpretation of «qigong» from the philosophical concept of integral harmony - Ruiz Morillas, Núria (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Qigong is a physical and a concentration exercise that has recently experienced a great expansion worldwide. This rapid diffusion has caused a transmission disconnected from its philosophical origin. In addition, a confused mixture of superficial concepts, related to physical and mental health is projected. This paper gives a new philosophical perspective to qigong using the concept of integral harmony of Fang Dongmei as a reference. The resulting essay gives a theoretical framework that brings a new and more consistent reading of qigong adapted to the present moment.